P‐86: Viewing‐Angle‐Enhanced Integral Imaging Display using Composite Micro‐Lens Array. Issue 1 (May 2016) - Zhang, Han-Le; Deng, Huan; Xing, Yan; Xiong, Zhao-Long; Wang, Qiong-Hua
Abstract : We propose a viewing‐angle‐enhanced integral imaging display using a composite micro‐lens array. The composite micro‐lens array is comprised a convex micro‐lens array and a concave micro‐lens array. The viewing angle along both the horizontal and vertical directions of the proposed display is enhanced by increasing the thickness of the concave micro‐lens and reducing the right radius of the concave micro‐lens. The maximum viewing angle of the proposed display is 4.36 times of the conventional one.